International Protection of Traditional Knowledge under the Law of Trademarks and Geographical Indications : A Case Study on Persian Carpets - Khademi, Hojjat (International Law E-Books Online, Collection 2025., 2025)
The open access publication of this book has been published with the support of the Swiss National Science Foundation. This comprehensive book explores how traditional knowledge (TK) intersects with global intellectual and ecological discussions within the framework of intellectual property rights (IPRs). Hojjat Khademi provides practical solutions for indigenous peoples and policymakers to protect and utilize TK effectively, including a detailed case study on Persian Carpets. With unique insights from key international organizations like WIPO and UNESCO, this text is an indispensable resource for legal scholars, students, and practitioners looking to understand and enhance TK protection under IPRs. Discover strategies to prevent TK misappropriation and promote fair legal frameworks worldwide.